POTENSI DAYA TARIK WISATA GODONG IJO SEBAGAI WISATA EDUKASI DI DEPOK JAWA BARAT - Veronika Br. Butar; Nova Eviana (LPPM and Travel Operation Department Universitas Asa Indonesia, 2017)
This research aims to analyze the potency of Godong Ijo as educational tourist object of West Java,by using SWOT analysis. The analysis identifies its strengths, weaknesses, threats, and opportunitiesas well. The result of the study shows that Godong Ijo needs to implement the aggressive strategy,whereas both strengths and opportunities are important elements to exaggerated